Data and text mining from online reviews - Moro, Sérgio (2022)
Moro, S., & Rita, P. (2022). Data and text mining from online reviews: An automatic literature analysis. Wiley Interdisciplinary Reviews: Data Mining and Knowledge Discovery. https://doi.org/10.1002/widm.1448 ----------------- Funding Information: The work by Sérgio Moro was supported by the Fundação para a Ciência e Tecnologia (FCT) within the following Projects: UIDB/04466/2020 and UIDP/04466/2020. The work by Paulo Rita was supported by the Fundação para a Ciência e a Tecnologia (FCT) within the Project: UIDB/04152/2020—Centro de Investigação em Gestão de Informação (MagIC). Publisher Copyright: © 2022 Wiley Periodicals LLC.